Considering the Evidence for Anterior and Laterodorsal Thalamic Nuclei as Higher Order Relays to Cortex - Perry, Brook A. L.; Mitchell, Anna S. (Frontiers in Molecular Neuroscience, 2019)
Our memories are essential in our daily lives. The frontal and cingulate cortices, hippocampal system and medial temporal lobes are key brain regions. In addition, severe amnesia also occurs after damage or dysfunction to the anterior thalamic nuclei; this subcortical thalamic hub is interconnected to these key cortical memory structures. Behavioural, anatomical, and physiological evidence across mammalian species has shown that interactions between the anterior thalamic nuclei, cortex and hippocampal formation are vital for spatial memory processing. Furthermore, the adjacent laterodorsal thalamic nucleus, interconnected to the retrosplenial cortex and visual system, also contributes to spatial memory in mammals. However, how these thalamic nuclei contribute to memory still remains largely unknown. Fortunately, our understanding of the importance of the thalamus in cognitive processes is being redefined, as widespread evidence challenges the established view of the thalamus as a passive relay of sensory and subcortical information to the cortex. In this review, we examine whether the anterior thalamic nuclei and the adjacent laterodorsal thalamic nuclei are suitable candidates for ‘higher-order’ thalamic nuclei, as defined by the Sherman and Guillery model. Rather than simply relaying information to cortex, ‘higher-order’ thalamic nuclei have a prominent role in cognition, as they can regulate how areas of the cortex interact with one another. These considerations along with a review of the latest research will be used to suggest future studies that will clarify the contributions that the anterior and laterodorsal thalamic nuclei have in supporting cortical functions during cognitive processes.